Ransomware: Analysis of 2019 LockerGoga cyber-attack to Norsk Hydro multinational company and its countermeasures - Akramova Nargiza (Genius Journals, 2022)
Norsk Hydro, the world`s largest aluminum manufacturing giant has recently been a victim of severe ransomware attack, which forced the business to close its operations worldwide in 40 countries and switch to manual operations. This cyber-attack caused severe disruption to business by making its network unavailable to its legitimate users. This paper critically discuss the origin of the breach, attack severity, attack vector used and the ways to prevent and mitigate such type of attack in future. The current research paper was composed through studying the previous case studies and the lessons learned regarding the ransomware and propose secure controls to ensure security of sensitive and confidential information of Norsk Hydro company. This paper can be of a great significance to researchers throughout the globe that are focusing on cyber-threat and ransomware studies, in particular in the business domain
Keywords: LockerGoga; Ransomware; cyber-attack; VM